The Awards almanac an international guide to career, research, and education funds. (Detroit, Mich. James Press, 1990)
Annual
Keywords: Continuing education -- Scholorships, fellowships, etc. -- Directories; Occupational training -- Scholorships, fellowships, etc. -- Directories; Scholarships -- Directories